The legal character of the Fund's stand-by arrangements and why it matters - Gold, Joseph (Washington, D.C. : International Monetary Fund, 1980)
This book is a stand by arrangement as a decision of the fund by which a member is assured the it will be able to make purchase from the general resource account.
Includes bibliographical references.
oo 18/04/2019
Loans